Research through play participatory methods in early childhood - Arnott, Lorna; Wall, Kate (SAGE Publications Ltd, 2021)
"Doing research with young children can be challenging for many reasons, but this book provides clear guidance on how to engage in appropriate methods. Focusing on researching through play, careful consideration is given to: · the founding principles of playful research · understanding young children's perspectives · prioritising the rights of the child and the voice of the child · examples of innovative research methods Real life examples and research projects are presented, to enable common challenges to be anticipated and to showcase successful creative approaches, and to inspire new paths in research"--